Heavy metals in sediment, microplastic and sea cucumber Apostichopus japonicus from farms in China. (June 2019) - Mohsen, Mohamed; Wang, Qing; Zhang, Libin; Sun, Lina; Lin, Chenggang; Yang, Hongsheng
Abstract: The concentrations of eight heavy metals (As, Cd, Cr, Cu, Mn, Ni, Pb and Zn) were measured in the sediment, the isolated microplastics from the sediment and the body wall of sea cucumbers from farms in China. Accordingly, the heavy metal concentrations in the sediment were below the class I upper limit of Chinese sediment quality guidelines. Among heavy metals, the median concentrations of Cd and As were higher in the body wall than in the corresponding sediment. Additionally, the median concentrations of Cd, Pb, and Zn were higher on the microplastics than in the corresponding sediment. Furthermore, there was no significant correlation among heavy metals in sediment, sea cucumber and microplastics. This study contributes to the understanding of the heavy metal accumulation in the sediment, the microplastics and the body wall of the sea cucumber. Graphical abstract: Unlabelled Image Highlights: Microplastics may serve as a vector of heavy metals in the sea cucumber farms. Sea cucumber may have a strategy accumulating some heavy metals in the body wall. Sea cucumber A. japonicus might be considered as a bio-monitor for Cd.